LUWES: land use planning for low emission development strategy: selected cases from Indonesia - Dewi, S.; Ekadinata, A.; Galudra G; Agung, P.; Johana, Feri (World Agroforestry Centre, 2011)
Opportunities for reducing greenhouse gas emissions exist across all sectors of the economy and across a wide geographic area, but emissions from forest and peatland conversion dominate the field, as well as the public debate. With the advent of REDD+, the introduction of an Indonesian action plan for emissions reduction under the remit of the Nationally Appropriate Mitigation Action (NAMA), and the potential for increased financial flows into carbon-rich landscapes, the question of how to relate national commitment to local context and effective implementation is more important than ever. Rather than focusing on short-term emissions reduction strategies, the debate has shifted towards new ‘clean development’ strategies that focus on maintaining high carbon stocks with low carbon flows, while still achieving development goals.